Mental Health Knowledge, Attitudes and Practices among Undergraduates in the University of Calabar, Cross-River State, Nigeria - Fidelis Takim Otu; Ijeoma Precious Chukwuwa; Donald Ikuwn Omang; Ekwen Odu Takim-Otu (International Journal of Global Health and Epidemiology, 2026)
Introduction: In recent years, there has been a steady rise in the prevalence of mental health issues globally, with the bulk of these issues affecting those between the ages of 15 and 24. Nigeria has become one of the world’s suicide hotspots, with a suicide rate of 17.3 per 100,000, higher above the worldwide (10.5 per 100,000) and African (12.0 per 100,000) rates. While studies on mental health knowledge and practices exist in developed countries and most Asian countries, empirical evidence on knowledge and practices towards mental health among young people in sub-Saharan Africa remains underexplored. Objective: This study determined mental health knowledge, attitudes and practices among undergraduates in University of Calabar, Nigeria. Method: A cross-sectional study design using quantitative method of data collection was used to collect data from 421 undergraduates, recruited using a multi-stage sampling procedure, using a validated semi-structured questionnaire. Descriptive statistics was used to summarize the data as frequencies and percentages using SPSS version 25. Results: Majority of the respondents, 247(59.0%), had good knowledge regarding mental health. Similarly, 247(59.2%) and 171(40.9%) had positive and negative attitudes towards mental health practices respectively. Also, 227(54.3%) exhibited good mental health promotion practices and 191(45.7%) exhibited poor practices towards mental health promotion. Conclusion: There is need for sustained mental health promotion awareness and education campaign as well as provision of mental health resources and services to improve the concerning knowledge level, attitude and practices towards mental health promotion of a significant number of the undergraduates.